The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ajco.13244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of purely accelerated six fractions per week radiotherapy in postoperative oral cavity squamous cell carcinoma

Abstract: No-EP 1132 (Titled "Toxicity analysis of pure modestly accelerated radiotherapy in post-operative oral cavity carcinomas") and published in Radiotherapy and Oncology (127) Supplement 1, Page S637. AbstractObjectives: Randomized controlled trials have shown improved loco-regional control (LRC) and disease-free survival (DFS) by modest acceleration using six fractions per-week radiotherapy (RT) as compared to conventional fractionation in patients of head and neck squamous cell carcinoma.We aimed to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
0
6
0
5
Order By: Relevance
“…On the other hand, RDT-induced hypopharyngeal mucositis is little studied. Only 4 studies on this subject were identified, in which patients presented oral squamous cell carcinoma with metastasis in cervical lymph nodes (10) , lung adenocarcinoma (11) , laryngeal carcinoma of squamous cells (12) and another, also in the oral cavity (13) , and in all cases, as a form of treatment, they underwent chemotherapy and radiotherapy in the head and neck region. The RDT dose received by the patients in the studies ranged from 30Gy to 66Gy, with an average of 60Gy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, RDT-induced hypopharyngeal mucositis is little studied. Only 4 studies on this subject were identified, in which patients presented oral squamous cell carcinoma with metastasis in cervical lymph nodes (10) , lung adenocarcinoma (11) , laryngeal carcinoma of squamous cells (12) and another, also in the oral cavity (13) , and in all cases, as a form of treatment, they underwent chemotherapy and radiotherapy in the head and neck region. The RDT dose received by the patients in the studies ranged from 30Gy to 66Gy, with an average of 60Gy.…”
Section: Discussionmentioning
confidence: 99%
“…In the last study analyzed (13) , patients were submitted to a total dose of 60 Gy, using three-dimensional conformal RDT. Throughout the radiotherapy treatment, 3 patients had to interrupt the RDT sessions, 2 of them due to grade 4 oropharyngeal mucositis and one of them due to grade 3 pharyngeal toxicity.…”
Section: Describe Upper Hypopharyngeal and Esophageal Ulceration Afte...mentioning
confidence: 99%
See 2 more Smart Citations
“…We read with interest the article by Rath et al 1 . The authors reported outcomes on 40 postoperative patients with oral cavity squamous cell cancer (OCSCC) with intermediate risk disease, treated with accelerated radiotherapy (ART) 60 Gy in 30 fractions in 5 weeks (six fractions per week, Monday to Saturday).…”
mentioning
confidence: 99%